PREDICTING MAXIMUM ENDURANCE OF A HIGH ALTITUDE LONG ENDURANCE UAV WITH TAGUCHI METHOD - ALI DINC; MEHDI MOAYYEDIAN (International Journal of Innovations in Engineering Research and Technology, 2021)
In this study, an application of Taguchi method was done on performance of a high altitude long endurance (HALE) unmanned air vehicle (UAV). General performance characteristics were calculated for UAV with a basic mission profile for a typical reconnaissance mission. Initially, endurance values of UAV were calculated and tabulated in an interval of airspeed and flight altitude. Then, Taguchi method was used to predict the maximum endurance on this interval. Secondly, flight range was calculated was calculated and tabulated at the same interval. On the implementation of the Taguchi method, two parameters in there levels were selected. Airspeed and flight altitude were the two parameters with assumed low, medium and high values. Taguchi method was found to be very effective in estimating the maximum values of flight endurance and the range of the UAV. Based on the response table of Taguchi, Speed was the most significant parameter and the optimum levels of the selected parameters to achieve the highest endurance were speed at level 1 and altitude at level 3. Also the percentage of contribution for speed and altitude was found to be 88.1% and 8.7% respectively.